New records of three alien Solanum species in Morocco - Hamid Khamar; Youssef Dallahi; Abdelmonaim Homrani Bakali (Check List, 2024)
Recent ﬂoristic surveys conducted in various regions of Morocco have revealed three new records of non-native vascular plants of the genus Solanum, namely, S. abutiloides Bitter & Lillo, S. bonariense L., and S. nitidibaccatum Bitter. The occurrence of these alien species in Morocco is documented here for the ﬁrst time. For each species, information on its national habitat and distribution are given. More-over, the distinguishing morphological features of these three species are compared with the most similar species (including Moroccan Solanum species).